Method for Accelerating Equilibrium in Perfectly Damped Brownian Motion with Harmonic Potential - Aszhar, Jodi; Setiawan, Iwan; Medriati, Rosane (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
Technological advances nowadays, making human beings able to do things easier and shorter. In this study, perfectly damped Brownian motion with a harmonic potential is considered, where previously it was moving randomly, requiring a long time to return to an equilibrium state. This research aims to determine the additional potential of each initial potential in the form of harmonic potentials with various powers. The method used is the Fast Forward method developed by Nakamura and Masuda. The equation used in this research is the Fokker-Planck equation. It was concluded that this research obtained additional potential for perfectly damped Brownian motion so that the time needed to reach the equilibrium state would be shorter.